Modeling of the system of continuing professional education on the regional and Federal levels - O. N. Petrova (Путеводитель предпринимателя)
In the article the questions of modeling of the system of continuous professional education of specialists in the sphere of social work at the Federal and regional levels. The basic principles and approaches to formation of system of continuous education, the data of sociological research.